ЎЗБЕКИСТОНДА ИҚТИСОДИЙ ТАЪЛИМ: КЕЧА, БУГУН ВА ЭРТАГА (Scientific journal of the Fergana State University, 2023)
Throughout the transition period to a market economy, economic education has been perfected in order to meet the challenges of the formation of market relations. The article attempts to generalize the experience of the past period in economic education, identify problems and provide recommendations for it’s improvement and development.